Owrzodzenia błony śluzowej i skóry jako pierwszy objaw toksyczności metotreksatu - B. Chavan, Ravindranath; Belgaumkar, Vasudha; P. Gosavi, Anil; Sanjay Deshmukh, Nitika; Bhatt, Neelam; Agrawal, Kopal (Dermatology Review/Przegląd Dermatologiczny, 2021)
We came across a 72-year-old man, who presented with oral intolerance to spicy food with raw areas over the lips and oral cavity and ulcers over pre-existing psoriatic plaques for the last 6 days. Detailed history revealed that he had taken daily doses of methotrexate (MTX) 7.5 mg twice a day without folic acid for 4 days (cumulative dose of 60 mg), the last dose taken 72 hours before presenting to us; without any proper prescription or instructions by a local practitioner. On examination, he had multiple erosions with haemorrhagic crusts on the lower lip and buccal mucosa (fig. 1) along with erythematous scaly plaques with partially healed ulcers over the extensor aspect of bilateral extremities (PASI 10.2) (fig. 2).A provisional diagnosis of plaque type psoriasis with acute MTX toxicity was made. Haemogram, serum albumin (3.6), serum albumin/globulin ratio (1.6), and liver and renal function tests were normal. Serum MTX level was 0.2 µmol/l. We administered intravenous fluids and folinic acid (30 mg/m2 over 2 to 3 hours, 3 doses 6 hourly) within 2 hours of presentation. Serum MTX level after 48 hours of folinic acid therapy was 0.01 µmol/l. The mucosal erosions resolved within 3 to 5 days. Considering higher risk of toxicity due to poor compliance and advanced age, the patient was started on tablets of apremilast 30 mg BD along with antacids. The treatment was well tolerated and his PASI score had decreased to 8.4 at the 1-month follow-up.